The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among U.S. Adults. (17th December 2021) - Fowler, Mackenzie; Wright, Nicole; Triebel, Kristen; Rocque, Gabrielle; Irvin, Ryan; Kennedy, Richard
Abstract: Cancer-related cognitive impairment is a common effect of cancer that shares symptoms with dementia. Only one study examined cancer's longitudinal association with dementia. This analysis expands to a larger clinical sample. Electronic health record data were extracted from July 2003-February 2020. Baseline cognition/progression on the Alabama Brief Cognitive Screener (ABCs) by cancer history were assessed using linear mixed effects models, with interaction by race. After adjustment for demographics/socioeconomics, those with cancer history had higher baseline cognition (⃞: 1.49 [0.91-2.07]), and declined slower (⃞: 0.40 [0.08-0.71]) than those without. Health behaviors/comorbidities attenuated this association. Non-Hispanic Blacks with cancer history demonstrated lower cognition throughout follow-up compared to non-Hispanic Whites / other race/ethnicities with cancer history and participants without cancer history. Health behaviors/comorbidities confound and race modifies the relationship between cancer and dementia. Exploring the role of health behaviors/comorbidities on this association and causes of racial disparities is needed.